2015
DOI: 10.1002/jbt.21685
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone Induces Apoptosis and Cell Cycle Arrest on Lung Squamous Cancer SK‐MES‐1 Cells

Abstract: Alantolactone, a sesquiterpene lactone compound, has variety of pharmacological properties, including anti-inflammatory and antineoplastic effects. In our study, alantolactone inhibited cancer cell proliferation. To explore the mechanisms underlying its antitumor action, we further examined apoptotic cells and cell cycle distribution using flow cytometry analysis. Alantolactone triggered apoptosis and induced cell cycle G1/G0 phase arrest. Furthermore, the expressions of caspases-8, -9, -3, PARP, and Bax were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Tumor cell toxicity is a well-known property of ATL, but the effective concentrations reported in the literature were very high, with IC 50 values ranging from 20 to 60 μM in various solid tumor cell lines [38][39][40]. In agreement with the literature, we found 10 μM ATL had no significant impact on the clonogenic growth of many human cancer cell lines ( Fig.…”
Section: Atl-induced Oxidative Dna Damage Activates Parp In Cancer Cellssupporting
confidence: 89%
“…Tumor cell toxicity is a well-known property of ATL, but the effective concentrations reported in the literature were very high, with IC 50 values ranging from 20 to 60 μM in various solid tumor cell lines [38][39][40]. In agreement with the literature, we found 10 μM ATL had no significant impact on the clonogenic growth of many human cancer cell lines ( Fig.…”
Section: Atl-induced Oxidative Dna Damage Activates Parp In Cancer Cellssupporting
confidence: 89%
“…Administration of alantolactone may be capable of inhibiting the Bcl-2/Bax signaling pathway in HeLa cells. Recent studies have suggested that alantolactone likely increases the ratio of Bcl-2 to Bax, therefore inducing apoptosis in cancer cells (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 in particular is required at the G1 to S phase. The overexpression of cyclin D1 can release cells from normal cell cycle control and cause a transformation to neoplasia [15,16]. Therefore, the protein level of cyclin D1 was detected by Western blotting.…”
Section: Effects Of β-Carotene On the Cell Cycle And The Expression Omentioning
confidence: 99%